Research on Back Pressure of Exhaust Gases for CMWF DPF - Bai Bing; Guo Xiurong; Wang Fenghu; Hou Xuling (2010 International Conference on Intelligent Computation Technology and Automation, 2010)
Airborne particulate matter is known for its environmental impact and is suspected of causing adverse health effects. Especially the role of ultra fine particles smaller than 0.1 mm, which amongst others is emitted by diesel engines, is the subject of current health related discussions. In order to solve this problem, many filtration methods have been researched, while so far the results are unsatisfactory. In this paper, a method of utilizing the carbonized micro-wood fiber (CMWF) as the filter material is presented and a corresponding mathematic model is built for the first time. Furthermore, the inertial coefficient and permeability of CMWF DPF are deduced. Theory and test prove that the theory method can be consistent with the test very well and CMWF DPF is very suitable for diesel exhaust gas purification.